The zero-magnetization Heusler ferrimagnet - COEY, JOHN; VENKATESAN, MUNUSWAMY; RODE, KARSTEN; ACKLAND, KARL (My University, 2013)
An unusual zero-moment half-metallic state has been predicted in stoichiometric Heusler compounds with 24 valence electrons, where, unlike an antiferromagnet, the two sublattices are chemically or crystallographically inequivalent. We have examined the following candidate materials: Cr2FeGe, Cr2CoGa, Fe2VGa, and Mn3Ga with various annealing and milling treatments. The Fe2VGa compound is identified as a weak itinerant ferromagnet, but both cubic Mn3Ga and perfectly ordered Cr2CoGa are potential zero-magnetization ferrimagnets.
PUBLISHED
Keywords: zero-magnetization ferrimagnets; zero-magnetization ferrimagnets